Achilles’ Inconsistency in Aristotle’s Lost Homeric Problems: a Fresh Look at Four bT-scholia of the Iliad - Mayhew, Robert (Hyperboreus, 2019)
My aim in this essay is to re-examine four bT-scholia of the Iliad, concerning the purported inconsistency of Achilles. Two of these have long been recognized as fragments from the Homeric Problems; but the other two, if my speculations are correct, might be previously unattested Aristotle-fragments. Eustathius plays an important supporting role in understanding these scholia, as do relevant passages in Aristotle’s Rhetoric and especially Poetics.